Guideline compliance in chronic heart failure patients with multiple comorbid diseases: evaluation of an individualised multidisciplinary model of care. - Tam H Ho; Gillian E Caughey; Sepehr Shakib (PLoS ONE)
Objective To assess the impact of individualised, reconciled evidence-based recommendations (IRERs) and multidisciplinary care in patients with chronic heart failure (CHF) on clinical guideline compliance for CHF and common comorbid conditions. Design and setting A retrospective hospital clinical audit conducted between 1st July 2006 and February 2011. Participants A total of 255 patients with a diagnosis of CHF who attended the Multidisciplinary Ambulatory Consulting Services (MACS) clinics, at the Royal Adelaide Hospital, were included. Main outcome measures Compliance with Australian clinical guideline recommendations for CHF, atrial fibrillation, diabetes mellitus and ischaemic heart disease. Results Study participants had a median of eight medical conditions (IQR 6-10) and were on an average of 10 (±4) unique medications. Compliance with clinical guideline recommendations for pharmacological therapy for CHF, comorbid atrial fibrillation, diabetes or ischaemic heart disease was high, ranging from 86% for lipid lowering therapy to 98% anti-platelet agents. For all conditions, compliance with lifestyle recommendations was lower than pharmacological therapy, ranging from no podiatry reviews for CHF patients with comorbid diabetes to 75% for heart failure education. Concordance with many guideline recommendations was significantly associated if the patient had IRERs determined, a greater number of recommendations, more clinic visits or if patients participated in a heart failure program. Conclusions Despite the high number of comorbid conditions and resulting complexity of the management, high compliance to clinical guideline recommendations was associated with IRER determination in older patients with CHF. Importantly these recommendations need to be communicated to the patient's general practitioner, regularly monitored and adjusted at clinic visits.